Solidarity and contention : networks of Polish opposition - Osa, Maryjane (Social movements, protest, and contention, 2003)
Solidarity and Contention deftly reconstructs the networks of protest in Communist Poland to show how waves of dissent during the 1950s, 1960s, and 1970s left an organizational residue that both instructed and enabled Solidarity and, ultimately, the Polish revolution. Using newly available documentary sources, Maryjane Osa shows how political challengers developed an ideological formula to facilitate coalition building.